Analysis of the Effectiveness of Artificial Intelligence Technology in Defect Prediction in Software Testing - Wu, Hao (Innovative Applications of AI, 2025)
With the continuous increase in the scale and complexity of software, software testing faces enormous challenges. Defect prediction, as a crucial part of software testing, plays a key role in improving software quality and reducing costs. This paper conducts an in-depth analysis of the application effectiveness of artificial intelligence technology in software testing defect prediction. It introduces the related principles and methods in detail and demonstrates their strengths and weaknesses through actual cases and data analysis. The aim is to provide a reference for the software industry to better utilize artificial intelligence technology for defect prediction.